(untitled) - Hữu Ngọc (Hà Nội, 2007)
This book is not just an eclectic potpourri. Mr Ngoc's brief introdution to vietnamese culture provides a context for the individual cultural traits he explores. Further, scholars, researchers and writes will be grateful for the index.
Keywords: Culture,Văn hóa; Vietnam